A Review of ex vivo Elemental Mapping Methods to Directly Image Changes in the Homeostasis of Diffusible Ions (Na+, K+, Mg2 +, Ca2 +, Cl–) Within Brain Tissue - Hartnell, David; Andrews, Wendy; Smith, Nicole; Jiang, Haibo; McAllum, Erin; Rajan, Ramesh; Colbourne, Frederick; Fitzgerald, Melinda; Lam, Virginie; Takechi, Ryusuke; Pushie, M. Jake; Kelly, Michael E.; et al. (Frontiers in Neuroscience, 2020)
Diffusible ions (Na+, K+, Mg2+, Ca2+, Cl-) are vital for healthy function of all cells, especially brain cells. Unfortunately, the diffusible nature of these ions renders them difficult to study with traditional microscopy approaches. This mini-review examines the recent progress in the field, using direct elemental mapping techniques to study ion homeostasis during normal brain physiology and pathophysiology. The mini-review examines the advantages and limitations of specific techniques: proton induced X-ray emission (PIXE), X-ray fluorescence microscopy (XFM), secondary ion mass spectrometry (SIMS), laser-ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), and the sample preparation requirements to study diffusible ions with these methods.